Beyond orphanhood: rethinking vulnerability in Ethiopia - Pells, K (Young Lives, 2011)
‘Orphans’ as a category of vulnerable children came to the fore in the context of the global AIDS crisis. Currently the notion of ‘Orphans and Vulnerable Children’ (or OVCs) dominates much of the child protection debates across sub-Saharan Africa. Data from Young Lives in Ethiopia challenges the assumption that parental death alone results in poorer life chances for children. While orphanhood can impact on children’s psychosocial well-being, socio-economic deprivation needs to be considered as well. Inequalities between children are greater due to poverty and household location, rather than between orphans and non-orphans. Tackling child poverty more broadly, rather than focusing exclusively on certain categories of children, needs to be at the heart of policies for children.